Miasto i procesy migracyjne we Francji - Hatzfeld , Marc (Człowiek i Społeczeństwo, 2014)
The author presents in a form of an essay the issues related to immigrant French suburbs in the context of their internal functioning. Areas generally considered to be non-integrated with the rest of the city and inhabited by a population non-integrated with the natives turn out to be the labs of new interpersonal relationships and ways to cope with otherness.